2017
DOI: 10.3390/su9060940
|View full text |Cite
|
Sign up to set email alerts
|

Addressing Large-Scale Energy Retrofit of a Building Stock via Representative Building Samples: Public and Private Perspectives

Abstract: Scientific literature about energy retrofit focuses on single buildings, but the investigation of whole building stocks is particularly worthy because it can yield substantial energy, environmental and economic benefits. Hence, how to address large-scale energy retrofit of existing building stocks? The paper handles this issue by employing a methodology that provides a robust energy analysis of building categories. This is denoted as SLABE, "Simulation-based Large-scale uncertainty/sensitivity Analysis of Buil… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
21
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 26 publications
(24 citation statements)
references
References 23 publications
0
21
0
Order By: Relevance
“…Case studies have shown the viability of the nZEB renovation measures to improve the condition of residential building stock in Croatia [5], Spain [6,7], Poland [8], and the Mediterranean climate [9]. The outcomes show huge potential energy and economic savings and support deep energy renovation needs [10,11].…”
Section: Introductionmentioning
confidence: 99%
“…Case studies have shown the viability of the nZEB renovation measures to improve the condition of residential building stock in Croatia [5], Spain [6,7], Poland [8], and the Mediterranean climate [9]. The outcomes show huge potential energy and economic savings and support deep energy renovation needs [10,11].…”
Section: Introductionmentioning
confidence: 99%
“…Article [6, [84][85][86][87][88][89][90][91] Conference paper [92][93][94][95][96][97][98][99][100][101][102][103][104][105] [ [106][107][108][109][110][111][112] Review [113][114][115][116][117] After every publication in Table 1 was accurately analyzed, it demonstrates that the methodologies employed are rather heterogeneous, and sometimes they even show conflicting results. Hardly any research proposes a comprehensive study, covering all the aspects that should be considered, from the early audits to the final decision-making processes.…”
Section: Type Of Document Not Open Access Open Accessmentioning
confidence: 99%
“…Three multi-function buildings in Bologna (Northern Italy) were selected as representative case studies, and the decision support system was tested on them. Another relevant work is presented in [84]; the authors analyzed an Italian building stock, creating 30 macro-categories of building typologies. The categories were defined according to five Italian climatic locations, three uses, and two types of envelope construction.…”
Section: Engineering Approaches In Building Stocksmentioning
confidence: 99%
“…Bre et al (2016) investigated the potential of residential building design optimisation using sensitivity analysis in Paraná, Brazil [35]. Ascione et al (2017) investigated the potential of large-scale energy retrofit measures on the building stock using sensitivity analysis techniques [36]. Chen et al (2017) performed a sensitivity analysis of passive design strategies for a high-rise residential building in the hot and humid climate of China [37].…”
Section: Introductionmentioning
confidence: 99%